Greening Career Pathways: A Policy Study on Green Human Resource Management and Its Impact on Young Talent Performance in Star-Rated Hotels in Semarang - Dyah Palupiningtyas; Krisnawati Setyaningrum Nugraheni; Euodia Bernike; Lidya Tristianti (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2025)
This study investigates the application of Green Human Resource Management (Green HRM) policies and practices within star-rated hotels in Semarang, Indonesia, and explores their influence on the performance and career progression of young professionals. Employing a qualitative methodology through a case study approach, data were collected from five star-rated hotels, with participants comprising HR managers, environmental supervisors, and early-career employees. The findings reveal that all five dimensions of Green HRM are being implemented across the sampled hotels, though with varying levels of intensity and consistency. The adoption of Green HRM practices positively contributes to organizational performance, particularly in enhancing operational efficiency, corporate image, regulatory compliance, and innovation in service delivery. For young talents, the integration of Green HRM fosters increased motivation, skill development, job satisfaction, and managerial recognition. Furthermore, Green HRM practices support career advancement by facilitating entry into environmental specialist roles, strengthening competitiveness in the labor market, accelerating promotion trajectories, and expanding professional networks. However, challenges in implementation persist, including constrained resources, organizational inertia, limited environmental expertise, and the absence of standardized performance metrics. This research contributes to the theoretical enrichment of Green HRM literature, particularly within the hospitality sector in emerging economies, and offers practical insights for both hotel practitioners and aspiring professionals.